Role of the Gd2O3 increment on the cerium oxidation state and luminescence behavior in the CeF3 doped silicoborate glass. (June 2023) - Intachai, N.; Wantana, N.; Kaewjaeng, S.; Kothan, S.; Kidkhunthod, P.; Chanlek, N.; Kim, H.J.; Kantuptim, P.; Yanagida, T.; Rajaramakrishna, R.; Kaewkhao, J.
Abstract: This study aimed to investigate the effect of Gd2 O3 on the cerium oxidation state and studied their luminescence in the silicoborate glass. Glass samples of a silicoborate glass containing cerium fluoride were prepared by doping the glass with varying amounts of Gd2 O3 in the chemical formula xGd2 O3 : 40Na2 O: 5SiO2 : (54.5)B2 O3 : 0.5CeF3 (x = 0.0, 2.5, 5.0, 7.5, and 10.0 mol%). Density and refractive index tend to increase with increasing Gd2 O3 content, whereas molar volume decreases. High-resolution XPS spectra confirm the chemical composition in the glass structure and found that the B1s and O1s regions illustrated more BO4 and bridging oxygen, respectively. X-ray absorption near edge structure (XANES) at the Ce LIII-edge was used to investigate the proportion between trivalent cerium (Ce 3+ ) and tetravalent cerium (Ce 4+ ). The ratio of Ce 3+ /Ce 4+ decreased with the addition of Gd2 O3 . A higher concentration of Gd2 O3 content showed more Ce 4+ related to the reduction of photoluminescence and X-ray-induced luminescence spectra. Alpha-induced luminescence was used to calculate the light yield of the 7.5Gd:0.5CeF glass. Decay time was measured by pulsed light sources at 286 nm and X-ray excitation. Highlights: Adding Gd2 O3 to B2 O3 leads one boron to change from B3 to B4 state. The creation of BO4 and bridging oxygen from added Gd2 O3 affected the oxidation states from Ce 3+ to Ce 4+ . The ratio of Ce 3+ /Ce 4+ decreased with the addition of Gd2 O3 . The behavior of Ce 4+ ions reduced the luminescence center of CeF3 -doped silicoborate glass.